Recapture and retreatment rates with ixekizumab after withdrawal of therapy in patients with axial spondyloarthritis: results at week 104 from a randomised placebo-controlled withdrawal study. Issue 2 (13th September 2022) - Landewé, Robert B M; Poddubnyy, Denis; Rahman, Proton; Van den Bosch, Filip E; Bolce, Rebecca; Liu Leage, Soyi; Lisse, Jeffrey R; Park, So Young; Gensler, Lianne
Abstract : Objectives: To evaluate the recapture of response with open-label (OL) ixekizumab (IXE) retreatment at week 104 in patients with axial spondyloarthritis who flared after withdrawal of IXE therapy. Methods: COAST-Y (NCT03129100 ) is a phase III extension study that included a double-blind, placebo-controlled, randomised withdrawal-retreatment period (RWRP). Patients who achieved remission (Ankylosing Spondylitis Disease Activity Score (ASDAS) <1.3 (inactive disease, ID) at least once at week 16 or 20 and <2.1 (low disease activity, LDA) at both visits) were randomised 2:1 at week 24 to continue IXE or withdraw to placebo. Patients who subsequently flared were switched to OL IXE every 2 or 4 weeks (Q2W or Q4W) at the next visit. The proportions of patients who recaptured ASDAS LDA and ID were summarised for those who experienced flare. Results: Of the 155 patients who entered the RWRP (placebo, n=53; IXE Q4W, n=48; IXE Q2W, n=54), 138 (89%) completed week 104. Of the placebo-treated patients (n=53), 28 (53%) experienced a flare during weeks 24–104; of these, 4 (14%) recaptured ASDAS LDA before retreatment with OL IXE, and 23 (82%) recaptured ASDAS LDA and 19 (68%) met ASDAS ID after retreatment. Of the continuously treated IXE patients (n=102), 13 experienced flare; 7 of 13 (54%) recaptured ASDAS LDA before switching to OL IXE retreatment, while 5 of 13 (38%) recaptured ASDAS LDA and 4 of 13 (31%) met ID after switching. Conclusions: Ninety-six per cent of patients withdrawn to placebo recaptured at least ASDAS LDA and 71% recaptured ASDAS ID with IXE retreatment at week 104. This may provide support to patients who may require a brief interruption in therapy.